Transceiver Architectures for W-CDMA Mobile Terminal Applications. - Thomann, Wolfgang; Fenk, Josef; Hagelauer, Richard; Weigel, Robert (Elektrotechnik und Informationstechnik, 2003)
Eligible transceiver architectures for third-generation Wide-Band Code Division Multiple Access (W-CDMA) mobile terminal application are presented. The heterodyne, homodyne, and low-IF architecture are discussed in detail with respect to their specific properties regarding W-CDMA. The considered issues include topics like system requirements, technical performance parameters, integration level possibilities as well as general topics like system cost and development effort.
elib2cris::1512001600,thomann2003
Keywords: W-CDMA; UMTS; Transceiver; Architekturen; Heterodyn; Homodyn